Correlation between Osteoarthritis Knee Damage Based on Ultrasound with Kellgren-Lawrence Classification - Wensri sevni Kurniawati; Muhammad Ilyas; Mirna Muis; Andi Alfian Z; Faridin Faridin; Sri Asriyani (Universitas Muhammadiyah Yogyakarta, 2021)
The classic standard criteria to diagnose osteoarthritis (OA) of the knee is the conventional radiological imaging. Ultrasonography could assess the osteoarthritis early and show invisible joint structures in osteoarthritis. This study aimed to compare the cartilage changes of trochlear femur and osteophytes (femur and tibia) through ultrasound examination with the radiological imaging in stages to Kellgren-Lawrence (KL) classification. This is an observational study using cross-sectional design, involved 33 patients with knee OA who underwent conventional photo examination and ultrasonography at dr. Wahidin Sudirohusodo Makassar Hospital in the period of June - August 2019. Spearman's test showed that there is a significant correlation between the stage of OA by KL and the stage of femoral trochlear cartilage damage (p 0.001) with strong correlation (r 0.828). Significant correlation is also between the stage of OA and the stage of osteophytes on the femur-lateral condylus both medial and lateral sides (p 0.001) with strong correlation (r 0.823; 0.79; 0.816, and 0.818). It concluded that the higher grade of femoral trochlear cartilage damage will result in the higher the stage of OA. The higher grade of osteophytes in knee joints will also result in the higher the stage of OA.